Macroeconomic Determinants and Institutional Factors Affecting Tax Revenue Performance: Evidence from ASEAN-5 Countries - Ardimansyah; Seprianda Risky (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
Taxation serves as a fundamental instrument for sustaining economic development by financing public expenditure and enhancing national fiscal capacity. This study examines the impact of macroeconomic and institutional factors on tax revenue performance across five ASEAN countries from 2000 to 2024. The analysis employs panel data regression with a fixed effects model, based on Chow and Hausman tests, to determine the most appropriate specification. The results reveal that gross domestic product, productive population, government expenditure, and trade openness have a positive effect on tax revenue, whereas inflation exerts a negative impact. Governance quality also demonstrates a significant role in strengthening fiscal capacity, as effective public administration and policy transparency enhance the credibility and efficiency of the taxation system. These findings underscore that macroeconomic stability, coupled with accountable and transparent governance, provides a solid foundation for enhancing tax revenue performance in the ASEAN-5 region and fostering sustainable economic growth.